Effects of the Portuguese Graphogame on reading, spelling, and phonological awareness in second graders struggling to read - Carvalhais, Lénia (2021)
The interest in computer-assisted interventions to promote literacy has increased over the years. In this study, we developed the Portuguese version of the GraphoGame Fluent and tested its effects on reading, spelling, and phonological awareness. Second graders struggling to read were randomly assigned to two groups: GraphoGame Fluent group (n = 15), which received a computer-assisted remedial reading intervention, or GraphoGame Math group (n = 15), which received a computer-assisted numeracy intervention. An additional, non-playing group, composed by second graders without reading difficulties, was formed (business-as-usual group, n = 15). Results showed clear benefits of GraphoGame on spelling and phonological awareness. After the intervention and one month later, the GraphoGame Fluent group displayed spelling and phonological awareness skills similar to the business-as-usual group, and above the GraphoGame Math group. Overall, these findings indicate that Portuguese struggling readers benefit from computer-assisted interventions that combine letter-sound correspondences with more complex orthographic patterns.